Management of Vacant Land Through the Planting of Green Vegetables Using Hydroponic Techniques as an Effort to Improve Community Economy - Arifin, Zainal; Makhmudah, Siti; Fauzi , Ahmad Masykurul; Rohmah, Ita Nur; Sari , Windi Erika; Huda, Chairul (Bisma : Bimbingan Swadaya Masyarakat, 2023)
The increasing demand for food and limited agricultural land in urban areas has prompted the exploration of alternative farming methods. This project focuses on utilizing vacant urban spaces for hydroponic farming as a sustainable solution to address food security and improve community economies. By implementing hydroponic systems in underutilized urban areas, the project aims to increase local food production, enhance community engagement, and promote sustainable agricultural practices. Through participatory action research (PAR), the community members were actively involved in the planning, installation, and management of the hydroponic systems, providing a hands-on learning experience. The results demonstrate that hydroponic systems significantly reduced water usage, maximized space efficiency, and increased crop yield compared to traditional farming methods. Furthermore, the project contributed to economic empowerment by generating income through the sale of produce and fostering local economic growth. The findings suggest that hydroponic farming in urban areas holds great potential for addressing food insecurity while promoting environmental sustainability and economic development.